Transport and Conductance in Fibonacci Graphene Superlattices with Electric and Magnetic Potentials. (May 2016) - Yin 尹, Yi-Heng 贻恒; Niu 牛, Yan-Xiong 燕雄; Ding 丁, Ming 铭; Liu 刘, Hai-Yue 海月; Liang 梁, Zhen-Jiang 振江
Abstract : We investigate the electron transport and conductance properties in Fibonacci quasi-periodic graphene superlattices with electrostatic barriers and magnetic vector potentials. It is found that a new Dirac point appears in the band structure of graphene superlattice and the position of the Dirac point is exactly located at the energy corresponding to the zero-averaged wave number. The magnetic and electric potentials modify the energy band structure and transmission spectrum in entirely diverse ways. In addition, the angular-dependent transmission is blocked by the potential barriers at certain incident angles due to the appearance of the evanescent states. The effects of lattice constants and different potentials on angular-averaged conductance are also discussed.